Shibori T-Shirt Training to Support Mental Health Rehabilitation and the Sustainability of Community Mental Health Posts : Pelatihan Kaos Shibori untuk Mendukung Rehabilitasi dan Keberlanjutan Posyandu Jiwa - Rosyad, Yafi Sabila; Istiyana; Prianto, Samsul Arif; Widagdo, Agus Haryanto (Bhakti Sabha Nusantara, 2025)
People with mental disorders (PWMD) often face limitations in social participation, productive activities, and economic independence, which may hinder their rehabilitation process within the community. This community service program aimed to support mental health rehabilitation and the sustainability of community mental health posts through Shibori T-shirt training for PWMD and community mental health cadres in Sembung Village, Wedi District, Central Java. The activity was conducted on 29 November and involved 30 participants, consisting of PWMD and mental health cadres. A participatory and educational approach was applied, integrating creative skill training with basic occupational therapy principles through hands-on practice of Shibori techniques, including fabric folding, tying, dyeing, and finishing processes. The results showed that most PWMD participants were able to follow the training stages and successfully produce at least one Shibori T-shirt with diverse patterns and colors. In addition to technical skill acquisition, the activity contributed to positive psychosocial outcomes, such as increased self-confidence, active participation, and improved social interaction between PWMD and mental health cadres. Cadres also perceived the training as a feasible and meaningful alternative activity to support community-based mental health programs. As a follow-up plan, the Shibori T-shirt production will be continued as official uniforms for the Community Mental Health Post to strengthen participants’ sense of belonging, program sustainability, and social inclusion. In conclusion, Shibori T-shirt training can serve as an effective creative empowerment strategy to support community-based mental health rehabilitation and enhance the sustainability of mental health services at the village level.